The Relationship between Individual Internal Factors and Work Fatigue among Employees of the Semarang City Health Office - Tiara Bethari Pramudya; Febriyanti Harianja; Siti Endah Wahyuningsih; Bayu Yoni Setyo Nugroho (Health Science Udinus, 2025)
Work fatigue is a physical and mental condition that leads to reduced work capacity and endurance and is often influenced by individual and job-related factors. This study aimed to analyze the association between individual internal factors (age, nutritional status, and length of service) and work fatigue among employees of the Public Health Division at the Semarang City Health Office. An analytical quantitative method with a cross-sectional design was employed in December 2025, involving all 31 employees as respondents. The independent variables were age, nutritional status measured by Body Mass Index (BMI), and length of service, while the dependent variable was the level of work fatigue measured using a reaction timer. Data were analyzed using the Spearman rank correlation test with a significance level of p < 0.05. The results showed that length of service (p = 0.020) and age (p = 0.030) had significant positive associations with work fatigue, whereas nutritional status (p = 0.257) was not significantly associated. Employees with longer tenure and older age tended to experience higher levels of work fatigue. In conclusion, work fatigue appears to be more strongly influenced by duration of employment and aging processes than by nutritional status. These findings highlight the importance of monitoring workload, providing periodic rest breaks, and managing job rotation to minimize fatigue and maintain employee productivity.